STRATEGI PEMERINTAH DESA DALAM MENGEMBANGKAN SEKTOR WISATA DI DUSUN SEMONGKAT DESA KELUNGKUNG KECAMATAN BATULANTEH - Rosyidah Rachman; Novi Kadewi Sumbawati; Anjasmara Anugra (Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study was to describe and analyze the Village Government Strategy in developing the tourism sector in Semongkat Hamlet, Klungkung Village, Batulanteh District. This study uses a qualitative descriptive approach with primary data types obtained from observations and interviews and documentation. The focus of this research is Strength, Weakness, Opportunity, Threat owned by Dusun Semongkat in the field of Tourism. The results of this study explain that Dusun Semongkat has a fairly good strength (Strength) of tourism potential and the government is more focused on building it, weaknesses (Weaknesses) of facilities and infrastructure that are still inadequate and a limited budget, opportunities (Opportunities) Situation, security and comfort of Hamlet Semongkat which is very conducive to the rapid development of mass media and technology as a means of supporting tourism in Semongkat Hamlet, the threat (Threats) of the rapid development and development of tourism outside Semongkat Hamlet as competitors is getting higher. There are several strategies to develop tourism in Semongkat Hamlet, increasing tourism promotion, developing tourism products, developing partnerships, developing through human resources.